Technology and Education: Impact on the Choice of University - Fondevila Gascón, Joan Francesc; Beriain Bañares, Ana; Del Olmo Arriaga, Josep Lluís (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
Technology is emerging as an essential tool for knowledge creation and social improvement. In the field of education, the inclusion of technology is essential in almost all areas. In this context it is important to analyze the weight of information and communication technology (ICT), such as the Internet, as a factor in student choice in access to college. In this paper we study the impact of the Internet and other formulas (references, visits, mass media) to get information in order to enter university, key decision for the younger generations of our society.